Analisis Pengelolaan “Filing System (Tata Persuratan) Dalam Meningkatkan Efektivitas Komunikasi di PT Dirgantara Indonesia” - Nabyla Seprilya; Fenny Damayanti (Jurnal Sekretaris dan Administrasi Bisnis, 2020)
This final report entitled "Analysis of Filing Systems in Improving the Effectiveness of Communication at PT Dirgantara Indonesia". This research is based on the background of the development of information technology that has advantages and positive impacts on communication. The more data that must be managed, stored, analyzed, and distributed, the quick and easy handling is needed. The development of information technology can create a filing system that is useful for companies. The purpose of writing this research is to find out how the management of the Filing System and how effective the filing system is in improving the effectiveness of communication at PT Dirgantara Indonesia, especially in the Directorate of Technology and Development. This type of research is descriptive qualitative. The writing of this research is based on 300 hours of practical work, data collection is obtained from direct observations, interviews with Secretary of Director Technology and Development and IT Staff, literature studies, and documentation. The results showed that PT Dirgantara Indonesia utilizing information technology by converting manual records into digital archives (filing system) was the right decision. This is evidenced by archives that are managed, stored well, neatly arranged and can increase the effectiveness of communication in PT Dirgantara Indonesia.